دور الأنشطة اللاصفية في تنمية التفكير الإبداعي لدى تلاميذ المرحلة الابتدائية من وجهة نظر أساتذة التعليم الابتدائي - مروة كرباع; صفاء الشيحي (جامعة الوادي - University of Eloued, 2025)
"هدفت الدراسة إلى التعرف على دور الأنشطة اللاصفية في تنمية التفكير الإبداعي لدى تلاميذ المرحلة الابتدائية من وجهة نظر الأساتذة، حيث تمت صياغة الإشكالية العامة على النحو التالي: هل تساهم الأنشطة اللاصفية في تنمية التفكير الإبداعي لدى تلاميذ المرحلة الابتدائية؟ تم إجراء الدراسة على عينة مقدرة ب 102معلم ومعلمة من سبع (7) ابتدائيات في بلدية حاسي خليفة ولاية الوادي، ولتحقق من فرضيات الدراسة تم استخدام المنهج الوصفي التحليلي، حيث تم استخدام استبيان لجمع البيانات للباحثة حلواني حيزية (2016) والذي احتوى على 25 بند مقسمة إلى ثلاثة محاور: محور الطلاقة، محور المرونة، محور الاصالة. كما اعتمدنا في معالجة البيانات احصائيا على الإحصاء البارامتري والإحصاء اللابارامتري وقد تم التوصل إلى النتائج التالية: - تساهم الأنشطة اللاصفية في تنمية التفكير الإبداعي لدى تلاميذ المرحلة الابتدائية من وجهة نظر الأساتذة. - تساهم الأنشطة اللاصفية في تنمية مهارة الطلاقة لدى تلاميذ المرحلة الابتدائية من وجهة نظر الأساتذة. - تساهم الأنشطة اللاصفية في تنمية مهارة الاصالة لدى تلاميذ المرحلة الابتدائية من وجهة نظر الأساتذة. - تساهم الأنشطة اللاصفية في تنمية مهارة المرونة لدى تلاميذ المرحلة الابتدائية من وجهة نظر الأساتذة. "The study aimed to identify the role of extracurricular activities in developing creative thinking among primary school students from the point of view of primary education teachers. The general problem was formulated as follows: Do extracurricular activities contribute to developing creative thinking among primary school students. The study was conducted on a sample estimated at 102 male and female teachers from seven (7) primary schools in the municipality of Hassi Khalifa, El Oued Province, to test the study hypotheses, the descriptive method was used, along with a questionnaire deveioped by researcher Halwani Hiziya (2016), which contained 25 items divided into three axes: the fluency axis, Flexibility axis, authenticity axis. In processing the data statistically, we also relied on parametric statistics and non-parametric statistics. The following results were reached: - Extracurricular activities contribute to developing creative thinking among primary school students from the teacher’s point of view. _Extracurricular activities contribute to developing the fluency skills of primary school students from the teachers’ point of view. _Extracurricular activities contribute to developing the skill of authenticity among primary school students from the teachers’ point of view. _ Extracurricular activities contribute to developing flexibility skills among primary school students from the teachers’ point of view
مذكرة ماستر قسم علم النفس وعلوم التربية تخصص إرشاد وتوجيه
Keywords: تلاميذ المرحلة الإبتدائية; الأنشطة اللاصفية; التفكير الإبداعي; Primary school pupils; creative thinking; extracurricular activities